Directive Illocutionary Acts In Best Health Podcast Entitled Talking To Your Kids About Coronavirus (Covid-19) - Mikhael Tri Purnama Petrus Tamang; I.G.A Vina Widiadnya Putri; Ni Nyoman Deni Ariyaningsih (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
This study is aimed to answer the research problem, which comprise: (1) To find out the types of directive illocutionary acts found in Best Health Podcast, (2) To describe the frequency of the types directive illocutionary acts in Best Health Podcast. The data in this research was taken from the utterance produced by Best Health and Dr. Linda Nicoletti in the Best Health Podcast entitled Talking to your kids about Coronavirus (COVID-19).This study used descriptive qualitative to analyze the data and quantitative method to find out about the frequency of type that implied in Best Health Podcast. The result of this analysis shows that there are 5 types of directive illocutionary act found in Best Health Podcast. There are advise, recommending, asking, requesting and telling. Based on the data, there are 31 directive illocutionary acts utterances found in this Podcast. Advise act becomes the most frequently produced by Best Health and Dr. Linda Nicoletti in Best Health Podcast. It holds 51,6% for all the percentage, and takes 16 utterances from 31 utterances. It takes the first rank of types of directive illocutionary acts used in Best Health Podcast. Then the least occurrence act is telling act. It only consists of 2 utterance and hold 6.4% from the whole percentage. So it can be conclude that advise act is the most successful way in expressing the speaker wishes over the hearer, and most frequently produced by Best Health and Dr. Linda Nicoletti in the Best Health Podcast.